2003
DOI: 10.1038/nm925
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cells from the adult mouse inner ear

Abstract: In mammals, the permanence of acquired hearing loss is mostly due to the incapacity of the cochlea to replace lost mechanoreceptor cells, or hair cells. In contrast, damaged vestibular organs can generate new hair cells, albeit in limited numbers. Here we show that the adult utricular sensory epithelium contains cells that display the characteristic features of stem cells. These inner ear stem cells have the capacity for self-renewal, and form spheres that express marker genes of the developing inner ear and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
353
2
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 427 publications
(380 citation statements)
references
References 39 publications
14
353
2
11
Order By: Relevance
“…Additionally, it is well known that the subventricular zone in the mammalian brain is a stem cell niche that give rise to neurons, as well as to glial cells, and that these multipotent stem cells even persist in the adult brain [45,46]. Although the presence of stem cells in the zebrafish ear has not been studied yet, a study conducted on adult mice demonstrated that cells from the inner ear can be considered as stem cells, since they are able to self-renew and to differentiate in a variety of cell types, including the hair cells responsible for the transmission of the hearing stimuli [47]. As drCol 15a1b is expressed in those locations where neural stem cells reside, it can be used as a novel stem cell marker for neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is well known that the subventricular zone in the mammalian brain is a stem cell niche that give rise to neurons, as well as to glial cells, and that these multipotent stem cells even persist in the adult brain [45,46]. Although the presence of stem cells in the zebrafish ear has not been studied yet, a study conducted on adult mice demonstrated that cells from the inner ear can be considered as stem cells, since they are able to self-renew and to differentiate in a variety of cell types, including the hair cells responsible for the transmission of the hearing stimuli [47]. As drCol 15a1b is expressed in those locations where neural stem cells reside, it can be used as a novel stem cell marker for neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that new hair cells could be formed by regeneration (e.g., Li et al, 2003) or phenotypic trans-differentiation (e.g., Gao, 2003;Izumikawa et al, 2005) within the adult mammalian inner ear. The regenerative potential of adult SGNs, however, remains to be tested.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, the cells with high proliferative index and pluripotency has been characterized in mouse vestibular sensory epithelia. 6 Moreover, the progenitor population of hair cells has been derived from the cochlea of neonatal rats. 7 Despite of the well-characterized pluripotency and stem cell-like property of supporting cells, stimulation of its trans-differentiating potential via medical approach for the therapeutic purpose is still challenging.…”
Section: Introductionmentioning
confidence: 99%